Surviving urban renewal program: Case study of a traditional urban village in Kuala Lumpur - Alhabshi, Sharifah Mariam (Institute of Tun Dr. Mahathir Mohamad’s Thoughts, Universiti Utara Malaysia Sintok, 2010)
The study undertakes an analysis of the development trajectory and outcomes of a 110 years Malay village located within Kuala Lumpur, Malaysia called Kampung Baru. More specifically the study seeks to account for the development paths of this village brought about by urbanization and planning. The village is characterized by relative tranquility and neat layout of traditional Malay houses, has relatively been retarded in its development with poor roads and sanitation even though the rest of metropolitan of Kuala Lumpur is enjoying a boom in economic growth and prosperity. The methodology that has been employed for this study relied on empirical field work that utilized both participant observation and a questionnaire survey. The research found political, historical and institutional factors has delayed planning and renewal of the (35,000 people and 153.35 km2) area. The consequence of the delay has been detrimental to landowners but advantages to non-owners and migrants who have been taking advantage of the area cheap rent and strategic location. The situation will soon change, however, for the city authority can no longer tolerate increasing criticism of the area disgracing image in the midst booming Kuala Lumpur city. Renewal is therefore certain but the fate of the village traditional image is uncertain.